SYNTHESIS OF ESTRONE-OPIOID PEPTIDE ANALOGUE WITH EXPECTED ANALGESIC ACTIVITY - AL-Hamashi, Ayad A; Saour, Kawkab Y (Al-Nahrain Journal of Science, 2010)
The search for new peptides to be used as analgesics in place of morphine has been mainlydirected to develop peptide analogues to have higher biological stability and receptor selectivity.Therefore extensive researches have been carried out on naturally occurring and syntheticopiates in order to enhance the analgesic potency, so we intended to prepare opioiod peptideanalogue linked to estrone which may increase the analgesic effect of this compound. Sterichindrance clearly will be produced by estrone may affect the enzymatic activity on the synthesizedanalogue and this in turn may enhance the bioavailability of the analogue itself, meanwhile estronemay affect physicochemical properties of the analogue by increasing its lipophilicity and sofacilitate its passage through the biological barriers, also estrone may affect receptor bindingselectivity of this analogue and decrease the side effect of the original opioid peptide.The designed analogue is (estrone-3-O-acyl-tyr-gly-gly-phe-met-OH), where this opioidpeptide synthesized following the conventional solution method, then linked to estrone by amidelinkage and it was characterized using: thin layer chromatography (TLC), melting point, infraredspectroscopy (IR), elemental microanalysis(CHN), optical rotation, amino acid analysis, andhydrogen-nuclear magnetic resonance(1H-NMR).